Pengaruh herbisida bentazon 400 g/l + mcpa 60 g/l terhadap gulma, pertumbuhan dan hasil tanaman padi (Oryza sativa L.) - Yayan Sumekar; Rian Suryana; Acep Atma Wijaya; Umar Dani (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2023)
Weeds are one of the obstacles in rice cultivation because they can reduce rice yields both in quality and quantity. Weeds compete in terms of necessities of life such as water, nutrients and sunlight. This study aims to determine the effect of betazon 400 g/l + MCPA 60 g/l in controlling weeds and the growth of paddy rice. The research was conducted in Palasah Village, Kertajati District, Majalengka Regency, West Java. The experiment used a one-factor Randomized Block Design (RBD) with seven treatments and four replications. The experiment consisted of five treatments of bentazone 400 g/l + MCPA 60 g/l at a dose of 1.5 L/ha, 2.0 L/ha, 2.5 L/ha, 3.0 L/ha, 3.5 L/ha, the comparison is in the form of manual control and without weed control. The data obtained if there is a significant difference will be further tested using the testDuncan Multiple Range Test (DMRT) at the level of 5%. The results showed that the application of the herbicide Bentazone 400 g/l + MCPA 60 g/l at a dose of 1.5 L/ha was able to suppress the growth of broadleaf weeds (Lindernia crustarcea, Spenoclia zeylanica and Marsilea crenata), sedge weeds (Cypress iria and Fimbristylis miliacea) and does not cause symptoms of toxicity (phytotoxicity) to rice plants which so that they do not interfere with their growth.